GENETIC DIVERSITY AND PHYLOGENETIC ANALYSES OF TURKISH RICE VARIETIES REVEALED BY ISSR MARKERS AND CHLOROPLAST trnL-F REGION - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2018)
A set of 17 Turkish rice (Oryza sativa L.) varieties (TRVs) were characterized using inter simple sequence repeat (ISSR) markers to study genetic diversity. Also, the sequences of trnL((UAA))-F-(GAA) intergenic spacer (IGS) regions were used to evaluate the phylogenetic relationships of TRVs. According to ISSR data, the observed number of alleles (Na), effective number of alleles (Ne), Nei's gene diversity (h), Shannon's information index (I), and overall polymorphism were found as 1.62, 1.38, 0.22, 0.32, and 61.7%, respectively. The genetic distance values were identified between 1.732and 4.583, and replicon size varied from 200 bp to 1600 bp. The ISSR-UPGMA (unweighted pair group method with arithmetic mean) similarity tree and PCA (principal component analysis) exhibited different cluster topologies based on pedigree. All trnL-F regions were found as 306 bp in length, and GC content was found between 34.31% and 34.97%. The nucleotide diversities were found as pi: 0.00954 and theta: 0.03595, while Tajima's D was found as -0.382. The phylogenetic analyses revealed that trnL-F sequences are effective molecular tools in resolving phylogenetic relationships. Consequently, our findings could be useful in planning future Turkish rice breeding strategies for general rice germplasm improvement.
Keywords: Oryza sativa; rice; genetic diversity; trnL-F; ISSR; SEQUENCE REPEAT ISSR; POPULATION-STRUCTURE; DNA; POLYMORPHISM; EVOLUTION; NUMBER; AFLP